Increased amplitude of low frequency fluctuations but normal hippocampal-default mode network connectivity in schizophrenia - Maureen eMcHugo; Baxter P Rogers; Pratik eTalati; Pratik eTalati; Neil D Woodward; Stephan eHeckers (Frontiers in Psychiatry, 2015)
Background: Clinical and preclinical studies have established that the hippocampus is hyperactive in schizophrenia, making it a possible biomarker for drug development. Increased hippocampal connectivity, which can be studied conveniently with resting state imaging, has been proposed as a readily accessible corollary of hippocampal hyperactivity. Here we tested the hypothesis that hippocampal activity and connectivity are increased in patients with schizophrenia.Methods: Sixty-three schizophrenia patients and 71 healthy control subjects completed a resting state functional magnetic resonance imaging scan. We assessed hippocampal activity with the amplitude of low frequency fluctuations. We analyzed hippocampal functional connectivity using three common methods: group and single subject level independent component analysis, and seed-based functional connectivity. Results: In patients with schizophrenia, we observed increased amplitude of low frequency fluctuations but normal hippocampal connectivity using independent component and seed-based analyses.Conclusions: Our results indicate that although intrinsic hippocampal activity may be increased in schizophrenia, this finding does not extend to functional connectivity. Neuroimaging methods that directly assess hippocampal activity may be more promising for the identification of a biomarker for schizophrenia.